Chloroplast Genome Sequence of Pigeonpea (Cajanus cajan (L.) Millspaugh) and Cajanus scarabaeoides (L.) Thouars: Genome Organization and Comparison with Other Legumes - Kaila, Tanvi; Chaduvla, Pavan K.; Saxena, Swati; Bahadur, Kaushlendra; Gahukar, Santosh J.; Chaudhury, Ashok; Sharma, T. R.; Singh, N. K.; Gaikwad, Kishor (Frontiers in Plant Science, 2016)
Pigeonpea (Cajanus cajan (L.) Millspaugh), a diploid (2n = 22) legume crop with a genome size of 852 Mbp, serves as an important source of human dietary protein especially in South East Asian and African regions. In this study, the draft chloroplast genomes of Cajanus cajan and Cajanus scarabaeoides were sequenced. Cajanus scarabaeoides is an important species of the Cajanus gene pool and has also been used for developing promising CMS system by different groups. A male sterile genotype harbouring the Cajanus scarabaeoides cytoplasm was used for sequencing the plastid genome. The cp genome of Cajanus cajan is 152,242bp long, having a quadripartite structure with LSC of 83,455 bp and SSC of 17,871 bp separated by IRs of 25,398 bp. Similarly, the cp genome of Cajanus scarabaeoides is 152,201bp long, having a quadripartite structure in which IRs of 25,402 bp length separates 83,423 bp of LSC and 17,854 bp of SSC. The pigeonpea cp genome contains 116 unique genes, including 30 tRNA, 4 rRNA, 78 predicted protein coding genes and 5 pseudogenes. A 50kb inversion was observed in the LSC region of pigeonpea cp genome, consistent with other legumes. Comparison of cp genome with other legumes revealed the contraction of IR boundaries due to the absence of rps19 gene in the IR region. Chloroplast SSRs were mined and a total of 280 and 292 cpSSRs were identified in Cajanus scarabaeoides and Cajanus cajan respectively. RNA editing was observed at 37 sites in both Cajanus scarabaeoides and Cajanus cajan, with maximum occurrence in the ndh genes. The pigeonpea cp genome sequence would be beneficial in providing informative molecular markers which can be utilized for genetic diversity analysis and aid in understanding the plant systematics studies among major grain legumes.